Low Concentration and High Transparency Keratin Hydrogel Fabricated via Cryoablation - Wang, Xiaoqing; Shi, Zhiming; Zhao, Le; Shen, Xianyi (Frontiers in Materials, 2021)
Keratins are highly attractive for medical applications due to their inherent self-assemblies characteristics and biocompatibility. However, nearly all researches have focused on the properties of hybrid hydrogels which was prepared from human hair keratin with other materials, and the preparation methods and properties of pure keratin hydrogels are rarely studied. Thus, we extracted keratins from rabbit hair, and a low concentration and high purity RHK hydrogel was then prepared by a simple freeze-thaw cycle and used to study gelation and the Optical properties. The results indicated that RHK keratin hydrogel is a reversible thixotropic system and elastic modulus the storage modulus (G′) substantially improves with freeze–thaw cycles. The systematic assessments including microstructural observation, porosity, and the secondary structure confirmed that the structure and properties of keratin hydrogels can be changed by controlling freeze-thaw cycles. Meanwhile, it is found that RHK hydrogel had high optical transmittance, and still maintained its fluorescent properties, which would be useful to observe the wound healing and locate the drug delivery process.